Bioinformatic profiling identifies the glutaminase to be a potential novel cuproptosis-related biomarker for glioma - Ouyang, Zhen; Zhang, Hanyi; Lin, Wenrui; Su, Juan; Wang, Xianggui (Frontiers in Cell and Developmental Biology, 2022)
Glioma is the most common tumour of the central nervous system, with a poor prognosis and an increasing trend of incidence in recent years; it is also beginning to affect younger age groups more. Added to this, cuproptosis is a new form of cell death. Indeed, when a certain amount of copper accumulates in a cell, it affects specific mitochondrial metabolic enzymes in that cell and leads to cell death – a phenomenon known as cuproptosis. In this study, we applied bioinformatics analysis, and, according to the results of the study analysis and Gene Ontology (GO), as well as the Kyoto Encyclopedia of Genes and Genomes (KEGG), the glutaminase (GLS) genes affect the prognosis, tumour mutation, and immune escape of glioma patients through cuproptosis. Glutaminase genes are a class of glucose metabolism-related genes that are involved in the tricarboxylic acid cycle of cells. At the same time, the expression of the glutaminase gene was positively correlated with the degree of immune cell infiltration and the expression of various immune cell markers, and thus affected the prognosis of glioma patients. Therefore, we believe that the cuproptosis-related glutaminase gene can be an important factor in determining the prognosis of glioma patients.